Comparison of Capillary and Venous Drug Concentrations After Administration of a Single Dose of Risperidone, Paliperidone, Quetiapine, Olanzapine, or Aripiprazole. Issue 6 (28th September 2016) - Remmerie, Bart; De Meulder, Marc; Weiner, Sveta; Savitz, Adam
Abstract: Risperidone, paliperidone, quetiapine, olanzapine, and aripiprazole are antipsychotic drugs approved for treating various psychiatric disorders, including schizophrenia. The objective of this randomized, parallel‐group, open‐label study was to compare finger‐stick‐based capillary with corresponding venous whole‐blood and plasma concentrations for these drugs after administration of a single dose to healthy volunteers. All whole‐blood and plasma drug concentrations were measured with validated liquid chromatography–tandem mass spectrometry methods. Capillary and venous concentrations (both in plasma and whole blood) were in close agreement, although a time‐dependent difference was observed, most obviously for olanzapine and paliperidone, with slightly higher capillary versus venous drug concentrations during the first hours after administering a single dose. The observed difference between capillary and venous plasma drug concentrations is expected not to be relevant in clinical practice, considering the wide window of therapeutic concentrations and the wide range of drug concentrations in the patient population for a given dose. Based on these results, finger‐stick‐based capillary drug concentrations have been shown to approximate venous drug concentrations.